Production of Drying Houses to Increase Dried Corn Production by Aur Serumpun Farmers Group - Daimon Syukri (Fakultas MIPA Universitas Negeri Padang, 2023)
Aur Serumpun farmers group is one of farmer group with their corn farming business. This farmer group is in Simpang Alahan Mati District, Kab. Pasaman, West Sumatra Province. So far, farmers only sell corn that has been dried. The processing of corn is a basic need for members of farmer groups in order to have product diversification which in turn can increase the economy of these farmers. In the previous activities (2019), it was known about processed corn products, namely tortilla chips. However, according to the needs of farmer groups, an increase in dry corn production is the most important. Therefore, in this 2022 activity, the activity of making Dryer houses for the Aur Serumpun Farmer Group was carried out. This development is a collaboration between Andalas University and the Farmers Group which is expected to increase the production capacity of dry corn because the use of drying houses can speed up the drying process. In 2022, a drying house with a size of 5 X 10 meters has been built and is very useful for the drying process, especially during the rainy season. The efficiency of using the tool will be carried out by involving students and carried out as an evaluation of this activity in the future.